2020
DOI: 10.1093/mnras/staa821
|View full text |Cite
|
Sign up to set email alerts
|

Hot phase generation by supernovae in ISM simulations: resolution, chemistry, and thermal conduction

Abstract: Supernovae (SN) generate hot gas in the interstellar medium (ISM), help setting the ISM structure and support the driving of outflows. It is important to resolve the hot gas generation for galaxy formation simulations at solar mass and sub-parsec resolution which realise individual supernova (SN) explosions with ambient densities varying by several orders of magnitude in a realistic multi-phase ISM. We test resolution requirements by simulating SN blast waves at three metallicities (Z = 0.01, 0.1 and 1Z ), six… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 101 publications
(166 reference statements)
5
50
0
Order By: Relevance
“…Changing the shape of the IMF from Salpeter to Chabrier slightly alters star-formation-related quantities (in agreement with e.g. Cassarà et al 2013), while varying wind velocities (Hassan & Gronke 2021) or SN efficiency has an impact of up to 1 dex when these parameters are varied by a factor of 5-10, independently of other model assumptions (Steinwandel et al 2020). For HI, the impact is less dramatic and results vary by less than 0.5 dex.…”
Section: Discussionsupporting
confidence: 60%
“…Changing the shape of the IMF from Salpeter to Chabrier slightly alters star-formation-related quantities (in agreement with e.g. Cassarà et al 2013), while varying wind velocities (Hassan & Gronke 2021) or SN efficiency has an impact of up to 1 dex when these parameters are varied by a factor of 5-10, independently of other model assumptions (Steinwandel et al 2020). For HI, the impact is less dramatic and results vary by less than 0.5 dex.…”
Section: Discussionsupporting
confidence: 60%
“…In cases where the SN remnant is resolved, the FIRE-2 subgrid model explicitly deposits the thermal energy expected from the energy-conserving phase, and allows the hydrodynamic solver to explicitly calculate the heating and momentum generation (𝑃𝑑𝑉 work). Note that while some small-scale simulations suggest that a resolution of < ∼ 100𝑀 may be necessary to properly capture the evolution of SN remnants (e.g., Kim & Ostriker 2015;Steinwandel et al 2020), the combination of multiple stellar feedback effects (e.g., early radiative feedback) with self-consistent clustering of star formation in FIRE-2 may act to alleviate this resolution requirement. Hopkins et al (2018a, Figure 9) showed that the FIRE subgrid model remains converged to the high-resolution result up to resolutions of 2000𝑀 for an m10 halo (see also Wheeler et al 2019, who re-simulated a few FIRE-2 dwarfs with 30𝑀 resolution).…”
Section: Simulation Descriptionmentioning
confidence: 99%
“…In order to launch strong outflows, the SFI has to be high enough, so that overlapping SN explosions create a volume-filling hot phase such that gas is removed in a thermally driven outflow. In the Milky Way and at the present epoch, the SFI is too low and disfavour the build-up of overlapping hot bubbles and the formation of strong outflows (Gatto et al 2015;L ie ta l .2015;Naab & Ostriker 2017;Steinwandel et al 2020). This has been demonstrated for example byKim&Ostriker(2015), Walch et al (2015), and Girichidis et al (2016) using high-resolution simulations of stratified galactic discs with multiple SN explosions.…”
Section: The Emergence Of Quiescent Discsmentioning
confidence: 85%